Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.ajpath.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Follicle Stimulating Hormone–Dependent Glyoxalase 1 Up-Regulation Sustains the Viability of Porcine Sertoli Cells through the Control of Hydroimidazolone– and Argpyrimidine-Mediated NF-κB Pathway

Abstract: Because Sertoli cells (SCs) play a central role in germ cell survival, their death may result in marked germ cell loss and infertility. SCs are the only somatic cells within the seminiferous tubules and are essential for regulating spermatogenesis. Factors that enhance or diminish the viability of SCs may have profound effects on spermatogenesis. Yet the mechanisms underlying the maintenance of SC viability remain largely unknown. Glyoxalase 1 (Glo1) detoxifies methylglyoxal (MG), a highly reactive carbonyl sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…Short-term treatment with high concentrations of MG has been reported to induce intracellular damage similar to that of hyperglycemia [ 15 ]. Therefore, via the glyoxalase pathway, the cellular detoxification of the reactive dicarbonyl metabolite, MG is essentially implemented [ 16 , 17 ]. In this pathway, Glo-1, a major MG detoxifying enzyme, catalyzes the first and the rate-limiting step in the removal of MG, and is crucial in protecting cells against oxidative stress [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Short-term treatment with high concentrations of MG has been reported to induce intracellular damage similar to that of hyperglycemia [ 15 ]. Therefore, via the glyoxalase pathway, the cellular detoxification of the reactive dicarbonyl metabolite, MG is essentially implemented [ 16 , 17 ]. In this pathway, Glo-1, a major MG detoxifying enzyme, catalyzes the first and the rate-limiting step in the removal of MG, and is crucial in protecting cells against oxidative stress [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…MG-derived dicarbonyl adducts exert complex pleiotropic effects on normal and pathologic processes in cells, including modulation of protein biological activity [3] and stability [4], and generation of reactive oxygen species (ROS) and oxidative stress [5], which may culminate in distinct biological outcomes [6,7,8,9,10,11]. In particular, supra-physiological accumulation of hydroimidazolone (MG-H1) and argpyrimidine (AP), AGEs originating from MG-mediated post-translational modification of proteins at arginine residues, has been shown to induce oxidative DNA damage and apoptosis [6,9,10,11]. However, post-translational modifications by MG-derived AP can also enhance the functionality of fundamental stress-inducible proteins implicated in cellular recovery after exposure to damaging stimuli and protection against apoptosis, including heat shock protein 27 (Hsp27), thus playing an important role in cell survival [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate possible mechanisms contributing to maintaining the BEAS-2B and A549 cell viability upon AuNPs exposure, we focused on Glo1, a cytoprotective enzyme whose function is to limit the intracellular accumulation of the potent pro-apoptotic agent, methylglyoxal (MG) [ 20 ]. In fact, when MG accumulates in cells at supra-physiological concentrations, it induces important post-translational modifications (PTM) that generates advanced glycation end-products (AGEs), such as hydroimidazolone (MG-H1), a heterogeneous family of compounds known to induce oxidative DNA damage and apoptosis [ 18 , 19 , 23 , 24 , 36 ]. We found that AuNPs exposure induced a significant increase of Glo1 enzyme activity, already at 3 h post-exposure, compared to the control cells in both cell lines ( Figure 3 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis was detected by measuring the activation of caspase-3, using an enzyme-linked immunosorbent assay (ELISA) (Thermo Fisher Scientific, Monza, Italy), specific for activated human caspase-3, following the manufacturer’s instructions [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation